Differential Diagnosis of Biliary Atresia and Other Causes of Neonatal Cholestasis: A 10-Year Clinical Experience - Zokirjon ugli, Nematjonov Farrukh; Muslimovich, Aliyev Makhmud; Urmonjonovich, Tuychiyev Golibjon; Zafarjanovich, Yuldashev Rustam; Anvarovich, Gofurov Adkham; Mukhammadjonova, Abduvaliyeva Chulponoy; Roksana, Shakirova (Journal of Neonatal Surgery, 2025)
Introduction Biliary atresia (BA) is a rare but severe fibro-obliterative disease of the bile ducts of unknown etiology, manifesting in the neonatal period. According to various sources, its incidence ranges from 1 in 5,000 to 1 in 22,000 live births [1–7]. BA is the leading cause of surgical (obstructive) cholestasis in infants and represents the most common indication for liver transplantation in pediatric patients [8]. Timely performance of the Kasai procedure (portoenterostomy) — preferably before the age of 60–90 days — significantly improves bile flow, slows the progression of fibrosis, and reduces the likelihood of requiring liver transplantation [9, 10]. However, early diagnosis of BA poses a significant clinical challenge, both in resource-limited settings and in well-developed healthcare systems. The main difficulty lies in differentiating BA from other causes of neonatal cholestasis — such as idiopathic neonatal hepatitis, progressive familial intrahepatic cholestasis (PFIC), Alagille syndrome, congenital hepatic fibrosis, cystic transformations of the common bile duct, as well as infections (e.g., CMV) and metabolic disorders [10–15]. All these conditions may present with similar clinical features: prolonged jaundice, acholic stools, and hepatomegaly. Among the biochemical markers of cholestasis, elevated levels of direct bilirubin, gamma-glutamyl transferase (GGT), and alkaline phosphatase are particularly important, although they are not specific and must be interpreted in combination with imaging findings [13]. Abdominal ultrasound (US) remains the primary method for initial diagnosis [16–18]. It allows evaluation of the shape and size of the gallbladder, identification of the "triangular cord sign" at the hepatic hilum, and the exclusion of other bile duct anomalies. However, the sensitivity and specificity of ultrasound depend on the operator's experience and may be reduced in the early stages of the disease. Additional diagnostic information can be obtained from magnetic resonance cholangiopancreatography (MRCP) and hepatobiliary scintigraphy, although the availability of these methods is often limited, especially in resource-constrained countries [19]. In recent years, transient elastography (TE) has been increasingly introduced as a non-invasive method to assess liver stiffness as an indirect marker of fibrosis severity [20, 21]. Given the rapid progression of fibrosis in BA, TE may serve as a valuable diagnostic tool. It is assumed that combining ultrasound and elastography improves the accuracy of early detection of BA and allows for timely referral for surgical intervention. However, data on the diagnostic effectiveness of this approach in resource-limited settings are still insufficient. Therefore, the aim of this study is to evaluate the diagnostic value of abdominal ultrasound and transient liver elastography in the early diagnosis of presumed biliary atresia in children with neonatal cholestasis, based on 10 years of clinical experience. Objective of the study. To evaluate the diagnostic criteria for biliary atresia (BA) and other causes of neonatal cholestasis in children based on 10 years of clinical experience. Materials and methods: The retrospective study included 157 neonates and infants with signs of cholestasis who were hospitalized at the Republican Specialized Scientific and Practical Medical Center of Pediatrics (Tashkent) between 2013 and 2023. The diagnostic algorithm included abdominal ultrasound (US), transient elastography (TE) of the liver, and, when indicated, hepatobiliary scintigraphy and MRI with cholangiography. The diagnosis of biliary atresia (BA) was surgically confirmed (via intraoperative cholangiography or liver biopsy) in 43 patients. In 88 other children, BA was considered probable based on a combination of clinical, laboratory, and imaging data. In the remaining patients, other diagnoses unrelated to BA were established using a comprehensive examination, including genetic testing in selected cases. Results: Presumed biliary atresia (BA) was diagnosed in 131 patients (83.4%), of whom 43 (32.8%) had the diagnosis surgically confirmed. The 'triangular cord sign' on ultrasound was detected in 38.3% of cases, and gallbladder abnormalities were found in 65.5%; however, in 35.8% of patients, the gallbladder appeared morphologically normal. The average liver stiffness value measured by transient elastography (TE) in children with presumed BA was significantly higher than in other forms of cholestasis (p<0.05), especially in patients older than 90 days. Among a subset of six patients who underwent scintigraphy, absence of intestinal excretion of the radiopharmaceutical was observed in all cases; BA was confirmed in four of them. MR cholangiography (n=12) revealed signs of the cystic form of BA, cystic transformation of the common bile duct, and syndromic BA with polysplenia. Conclusion: The combination of ultrasound examination and transient elastography improves the accuracy of early diagnosis of presumed biliary atresia. However, a comprehensive approach that takes into account laboratory findings and additional imaging methods is crucial for timely differentiation of BA from other causes of cholestasis and for determining the optimal treatment strategy.